Inventory Discrepancy Risk Analysis and Mitigation Prioritization at Finished Goods Warehouse Using the House of Risk Method - Resi Khalisya Wildani; Siti Rahayu; Rini Siskayanti (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
Inventory discrepancy in finished goods warehouses reduces inventory accuracy and may disrupt warehouse operations and product distribution. This study was conducted at PT Alpha Plastic Manufacturing (a pseudonym), a plastic injection moulding company operating in the plastic manufacturing sector that manages a finished goods warehouse for injection-moulded components supplied for industrial applications. This study aims to analyze the causes of inventory discrepancy and determine appropriate mitigation strategies by integrating the Supply Chain Operations Reference (SCOR) model and the House of Risk (HOR) method. A descriptive quantitative approach was employed using observation, interviews, focus group discussions, company documents, and questionnaires involving three warehouse experts. The SCOR model was used to identify risk events and risk agents, while HOR Phase 1 prioritized risk agents using Aggregate Risk Potential (ARP), and HOR Phase 2 determined preventive actions based on the Effectiveness-to-Difficulty Ratio (ETD). The integration of SCOR and HOR provides a systematic approach to connect warehouse operational activities, priority risk sources, and feasible mitigation strategies. The results identified 10 risk events and 8 risk agents, with six priority risk agents contributing 86.36% of the total ARP value and five priority preventive actions contributing 66.97% of the total ETD value. Based on the investigated case, the findings indicate that strengthening warehouse procedures and operational controls should become the initial priority for reducing inventory discrepancy before implementing advanced inventory technologies.